Servelle-martorell syndrome with severe orthostatic hypotension in a pediatric patient - Yuri Igor Lopez-Carrera; Max Bernal-Moreno; Oscar Colin; María Teresa García-Romero; Carola Durán-McKinster (Wolters Kluwer Medknow Publications, 2017)
Servelle-Martorell syndrome (SMS) is an extremely uncommon vascular malformation characterized by venous malformations (VMs), limb overgrowth, and bone hypotrophy. The most common complications are venous thrombosis and pathological fractures. Ectasia and aneurysmal dilatations of the superficial veins may result in overgrowth of soft tissues but shortening of the affected limb. We report an 11-year-old Hispanic boy with an enlarged lower limb and VM. The patient suffered a fall at 9 years of age resulting in ankylosis of the knee without the possibility of limb extension or walking. When he tried to stand up, a severe orthostatic hypotension and almost loss of consciousness were present. An angio computed tomography and an arteriography demonstrated a complete absence of the deep venous system and bony hypotrophy compatible with SMS.